Existence, uniqueness and continuity of portfolio choice - Laurie Davies; Gerd Ronning (Universität Konstanz, Fachbereich Wirtschaftswissenschaften, 1973)
Under fairly weak conditions it is shown that an optimal portfolio choice exists and is unique. It is further shown that this choice is a continuous function of the joint distribution function of the random returns on the assets from which the choice is made.
Keywords: 330